Arterial stiffness and its associations with left ventricular diastolic function according to heart failure types - Kim, Hack-Lyoung; Chung, Jaehoon; Han, Seokmoon; Joh, Hyun Sung; Lim, Woo-Hyun; Seo, Jae-Bin; Kim, Sang-Hyun; Zo, Joo-Hee; Kim, Myung-A (Clinical hypertension, 2023)
Background Little is known about the characteristics of arterial stiffness in heart failure (HF). This study was performed to compare the degree of arterial stiffness and its association with left ventricular (LV) diastolic function among three groups: control subjects, patients with HF with reduced ejection fraction (HFrEF), and patients with HF with preserved ejection fraction (HFpEF). Methods A total of 83 patients with HFrEF, 68 patients with HFpEF, and 84 control subjects were analyzed. All HF patients had a history of hospitalization for HF treatment. Brachial-ankle pulse wave velocity (baPWV) measurement and transthoracic echocardiography were performed at the same day in a stable condition. Results The baPWV was significantly higher in patients with both HFrEF and HFpEF compared to control subjects (1,661 ± 390, 1,909 ± 466, and 1,477 ± 296 cm/sec, respectively; P < 0.05 for each). After adjustment of age, baPWV values were similar between patients with HFrEF and HFpEF ( P = 0.948). In the multiple linear regression analysis, baPWV was significantly associated with both septal e′ velocity (β = –0.360, P = 0.001) and E/e′ (β = 0.344, P = 0.001). However, baPWV was not associated with either of the diastolic indices in HFrEF group. The baPWV was associated only with septal e′ velocity (β = –0.429, P = 0.002) but not with E/e′ in the HFpEF group in the same multivariable analysis. Conclusions Although arterial stiffness was increased, its association with LV diastolic function was attenuated in HF patients compared to control subjects. The degree of arterial stiffening was similar between HFrEF and HFpEF.